Dissecting the circuitry of the auditory system - Pollak, George D; Burger, R.Michael; Klug, Achim (Trends in neurosciences (Regular ed.), 2003)
The brainstem auditory system is a complex system composed of numerous parallel and serial pathways that converge on a common destination in the inferior colliculus (IC). The exact nature of the response transformations that occur in the IC have, however, been elusive – even though the IC has been the subject of numerous studies for more than 30 years. Recent studies have addressed this issue by recording from IC neurons before and during micro-iontophoresis of drugs that selectively block GABA A or glycine receptors (the dominant inhibitory receptors in the IC) or by reversibly inactivating a lower nucleus that provides inhibitory innervation to the IC. These studies have revealed some of the ways that signals, relayed via many different parallel routes, interact in the IC, and suggest some functional advantages that these interactions might have.